3D Printing: Activated Carbon in the Third Dimension—3D Printing of a Tuned Porous Carbon (Adv. Sci. 19/2019) - Steldinger, Hendryk (Adv Sci (Weinh), 2019)
In article number 1901340, Bastian J. M. Etzold and co‐workers employ stereolithography 3D printing to enhance activated carbon to the 3D dimension. Enabling true co‐polymerization and porogen templating during the printing allows carbon structures to be obtained with controlled geometry from the µm to mm scale in combination with porosity down to the nm scale and surface areas of 5 tennis courts per 1 g. [Image: see text]